Potoczność w obrazie wiary w Boga na podstawie wypowiedzi współczesnych Polaków - Grabowska, Magdalena (Słowo. Studia językoznawcze, 2014)
The paper discusses the problem of colloquial, naive thinking and conceptualization in the description of the concept of faith in God. On the basis of the research material (questionnaires and interviews) acquired from Polish Christian believers, I try to unearth the unconscious, common image of faith in God. I confront the existing definitions of faith in God with the variants emerging from the collected data. I also take into account the Biblical account of faith. According to ethnolinguistic assumptions, everyday language reveals colloquial thinking and naive perception of the world typical of a given society. Colloquial language is the most natural form of language and communication to which all people adhere. On the other hand, the research data is not free from symptoms of more scientific approach to the notion in question.